2015
DOI: 10.1021/acs.orglett.5b00858
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Highly Functionalized BOPHY Chromophores Displaying Large Stokes Shifts

Abstract: BOPHY dyes bearing bromo (in 5,5'-position) and iodo (in 4,4'-position) were synthesized. Double Knoevenagel reactions allow the extension of conjugation, resulting in an absorption above 625 nm. Selective cross-coupling reactions promoted by palladium(0) and microwave irradiation allow linking of a perylene module. These dyes are highly fluorescent, and the intramolecular cascade energy transfer from the perylene moiety to the BOPHY framework is almost quantitative, providing large virtual Stoke shifts (>5100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(63 citation statements)
references
References 23 publications
2
61
0
Order By: Relevance
“…To address this issue, great effects have been dedicated and a number of noted uorophore dyes with large Stokes shi (Dl $ 80 nm) have been developed. [24][25][26][27][28] However, some problems are encountered with them containing complicated structures, multi-steps reaction, and low yields.…”
Section: Introductionmentioning
confidence: 99%
“…To address this issue, great effects have been dedicated and a number of noted uorophore dyes with large Stokes shi (Dl $ 80 nm) have been developed. [24][25][26][27][28] However, some problems are encountered with them containing complicated structures, multi-steps reaction, and low yields.…”
Section: Introductionmentioning
confidence: 99%
“…Ziessel et al have reported [13] on the properties of the first molecular dyad built around the BOPHY scaffold (Figure 8). Here, a perylene moiety has been linked to the BOPHY core by way of an ethynylene group, thereby ensuring both close proximity and strong π-conjugation.…”
Section: Symmetrical Pyrrole-bf 2 (Bophy) Modulesmentioning
confidence: 99%
“…The first review paper on BOPHY was published in 2018 [10]. BODIPY is a typical member of FBC, which has received great interests owing to its excellent photo-stability and thermo-stability [11][12][13]. As far as we know, no halogenated BOPHY derivative has been reported.…”
Section: Commentmentioning
confidence: 99%